Sistem Aplikasi Penjualan Gula Aren Berbasis Web Menggunakan Framework Flask - Izzathohir, Khamid Miftakhul; Yulianton, Heribertus (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The development of computer technology has influenced various aspects of life, including the field of trade. One local product that is experiencing increasing demand is palm sugar, both in the domestic and international markets. However, palm sugar sales and distribution management is still faced with challenges such as limited access to information, inefficient inventory monitoring, and a lack of centralized system integration. This research aims to design and develop a web-based palm sugar sales application system to increase the efficiency and effectiveness of sales management. This application system uses the Flask Python framework, which is a lightweight and easy-to-use web framework. By implementing important features in the sales system and providing an intuitive user interface, this system can help increase operational efficiency in palm sugar sales management. The flexibility provided by the Flask Python framework allows developing and customizing the system according to different business needs